Etiology, Clinical Phenotypes, Epidemiological Correlates, Laboratory Biomarkers and Diagnostic Challenges of Pediatric Viral Meningitis: Descriptive Review - Al-Qahtani, Saleh M.; Shati, Ayed A.; Alqahtani, Youssef A.; Ali, Abdelwahid Saeed (Frontiers in Pediatrics, 2022)
Meningitis is an inflammation of the brain and spinal cord meninges caused by infectious and non-infectious agents. Infectious agents causing meningitis include viruses, bacteria, and fungi. Viral meningitis (VM), also termed aseptic meningitis, is caused by some viruses, such as enteroviruses (EVs), herpesviruses, influenza viruses, and arboviruses. However, EVs represent the primary cause of VM. The clinical symptoms of this neurological disorder may rapidly be observed after the onset of the disease, or take prolonged time to develop. The primary clinical manifestations of VM include common flu-like symptoms of headache, photophobia, fever, nuchal rigidity, myalgia, and fatigue. The severity of these symptoms depends on the patient’s age; they are more severe among infants and children. The course of infection of VM varies between asymptomatic, mild, critically ill, and fatal disease. Morbidities and mortalities of VM are dependent on the early recognition and treatment of the disease. There were no significant distinctions in the clinical phenotypes and symptoms between VM and meningitis due to other causative agents. To date, the pathophysiological mechanisms of VM are unclear. In this scientific communication, a descriptive review was performed to give an overview of pediatric viral meningitis (PVM). PVM may occasionally result in severe neurological consequences such as mental retardation and death. Clinical examinations, including Kernig's, Brudzinski's, and nuchal rigidity signs, were attempted to determine the clinical course of PVM with various success rates revealed. Some epidemiological correlates of PVM were adequately reviewed and presented in this report. They were seen depending mainly on the causative virus. The abnormal cytological and biochemical features of PVM were also discussed and showed potentials to distinguish PVM from pediatric bacterial meningitis (PBM). The pathological, developmental, behavioral, and neuropsychological complications of PVM were also presented. All the previously utilized techniques for the etiological diagnosis of PVM which include virology, serology, biochemistry, and radiology, were presented and discussed to determine their efficiencies and limitations. Finally, molecular testing, mainly PCR, was introduced and showed 100% sensitivity rates.